The Woman Under Virtual Reality Environment - عفاف بديع القدو فرح عبد الامير فرح رافد (College of Education for Women, 2019)
Virtual reality technology is the science of the embodiment of things and move spontaneously among non-real from one place to another with the full sense of the form, touch, sound, enables the user tried out and deal with it, like a real natural world and open up new worlds for human ambitious to let him overlooks the supposed world. Internet has become part of our daily lives, especially with the presence of mobile devices; that revolutionized the world of social networking. Access to information and build relationships change in the era of digital technology. The woman is not in isolation from this era; she found to herself a wide area for the production of ideas. When we talk about woman in the modern means of communication, this affects the entire community without addressing the specific area. The reality of the situation of woman with regard to modern means of communication similar in terms of motivation and the events, and results with men, but the case is one. Woman found enlist through this virtual platform, using its capabilities to defend the issues and express her that made her voice heard and achievements on more than one levelchanged the stereotype at least partially about the reality of the woman who has proved the case that she can be a real partner in the human construction. A woman adds to her role as a housewife new role characterized by her cultural, intellectual and political production across the Internet making her rebel against the powers of time and space exploiting this virtual reality to elevating will. So coupled interaction with the desire to change and thus express their demands and defend their right in function construction humanitarian. This virtual world open on the other has its advantages and disadvantages, how women cope with this world coming from the womb of the future? In this research the pros and cons of women's use virtual reality was studied and explain the motives and reasons that make many women use the Internet and the result reached by the research are: that the most important reasons and motives emptiness emotional, too much leisure time, trouble marital and family disappointments and finally out of the barriers and community restrictions in the reality, where most of them use of fake names because of their inability to face the family arguing that the demand-oriented woman to use the Internet because she can not disclose inside and that the idea which she believes cannot be expressed only in that virtual world in which enlist find to express herself. They are at the storming of the unknown world become susceptible to many of the risks of non-feel. These risks in the simplest effects lead to non-intellectual and emotional balance, which negatively affects her family and especially her marriage and that leads to the loss of many of the gains of her life and that cannot be compensated in any way But this does not mean that there are a lot who have the awareness and culture and deep vision to the use of this virtual world on the Internet by blogging to express their positions and connect their vision and mission that contribute to the benefit of society. Whether those that did not complete the study, but trying to keep pace via the internet the progress and global development, or those who studied and received the highest certification she entered the blogging world, scientific and literary websites to reach her scientific and literary ideas, and looked forward to each new. The electronic sites benefit the modern women in the dissemination of her ideas and see the all-new. The women need only to choose the best and more benefit sites. This requires their aware in order not to fall into the trap of choosing the stereotypical images. Everything is possible, but it awareness is necessary.